An investigation of tillage systems and implement design for water conservation in semi arid conditions in Botswana - Kethobile, Elias (Cranfield University, 2006)
Botswana, as a semi arid country, is faced with serious shortage of moisture for crop production. Its challenging climatic condition makes the little moisture received from summer rainfall insufficient. The development of appropriate tillage systems can assist with sustainable crop production. The aim of this project was to come up with a tillage system to improve the suitability of the physical conditions of soil for effective seeding in rain fed farming in Botswana. Strip, Reservoir (depression) and no tillage systems (control) were therefore investigated. Laboratory investigation of the tillage systems for soil water conservation and erosion was undertaken under different slopes (5 and 10°) and rainfall intensities (55 and 95 mm/hr). Energy requirements and work rates of the systems were analysed. The results showed that slope has effects on the capability of strip tillage to harvest water from rainfall of low intensity. It managed to harvest 69.12% of rainfall from 55mm/hr rainfall at a slope of 5° whereas at 10°slope it harvested about 49%. The effects of slope were not significant for the reservoir tillage and no tillage systems. Under a higher intensity rainfall of 95mm/hr the effects of slope were insignificant. The only source of variance was due soil disturbances and the strip soil disturbance performed better than the other treatments. When eroded soil was investigated under low intensity rainfall (55 mm/hr), there was no significant difference between strip and depression. Depression and strip soil disturbances reduced soil erosion similarly by 47 and 46 % respectively. Under high intensity rainfall eroded soil was still high under undisturbed soil disturbance. This is due to the fact that when the soil surface is bare, there is a higher risk of soil erosion. But when strips and depression are created, the risk of soil erosion is localised especially at high rainfall intensities. The evaporation analysis showed no significant difference among the tillage systems. This means that the power of water conservation in semi arid environment lies more on water harvesting than reduction of evaporation.The analysis of power and work rates showed big advantage of strip tillage system over reservoir tillage in the sense that it required less energy and power to complete a hectare of land. Its work rate is almost double of strip tillage. From the results it can be concluded that, at low slope and low rainfall intensity strip tillage harvest more water than reservoir tillage and zero tillage systems. When slope is elevated there is no difference between strip and reservoir tillage. The strip tillage system harvest more water than both reservoir tillage and zero tillage at high intensities. Strip and reservoir tillage reduce soil erosion similarly at both low rainfall and high rainfall intensity. The energy requirements and work rate were more positive for strip tillage that reservoir tillage. Therefore with these results a conceptual design of strip tillage system was developed.